2022
DOI: 10.3390/ijms23169127
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Topiramate in a Chronic Model of TNBS-Induced Colitis

Abstract: Inflammatory bowel disease (IBD) is characterized by a chronic and relapsing inflammatory response in the gastrointestinal tract, resulting in severe symptoms such as abdominal pain, vomiting, diarrhea, bloody stools, and weight loss. Currently, there is no cure, and the pharmacological treatment includes drugs that induce and keep the patient in remission, not reversing the underlying pathogenic mechanism. These therapies, in the long term, may cause various side effects and complications, which has increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Among experimental studies focused on gastrointestinal diseases found in the literature, IIRI-and 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats appears as a current model used by many authors and research groups around the world. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] For this reason, we selected these two relevant pathologies to evaluate the experimental BK procedure in an intestinal injury scenario. IIRI was used for simulating a model of intestinal intussusception, strangulated hernia or intestinal transplantation.…”
Section: Step 2 Bk Model Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among experimental studies focused on gastrointestinal diseases found in the literature, IIRI-and 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats appears as a current model used by many authors and research groups around the world. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] For this reason, we selected these two relevant pathologies to evaluate the experimental BK procedure in an intestinal injury scenario. IIRI was used for simulating a model of intestinal intussusception, strangulated hernia or intestinal transplantation.…”
Section: Step 2 Bk Model Applicationmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The same situation occurs in the field of experimental colitis, where old and recent scientific articles use one animal in each LI sample collection. [30][31][32][33][34][35][36][37] For the reasons mentioned above, it is a challenge to develop models that enable reducing the number of animals involved in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Este es un modelo experimental de interés de investigación en la actualidad entre las patología de intestino grueso utilizado por múltiples autores y grupos de investigación. (104)(105)(106)(107)(108)(109)(110)(111) Materiales y métodos: Se constituyeron tres grupos compuestos por ratas Sprague-Dawley hembras (peso 190 ± 2,6 gr). A las cuales se les realizó la técnica de BK en la porción distal del intestino grueso.…”
Section: Bk En Un Modelo De Colitis Inducido Por Tnbsunclassified